2018
DOI: 10.1111/ppl.12728
|View full text |Cite
|
Sign up to set email alerts
|

The role of C2H2 zinc finger proteins in plant responses to abiotic stresses

Abstract: Abiotic stresses are important factors affecting plant growth and development and limiting agricultural production worldwide. Plants have evolved complex regulatory mechanisms to respond and adapt to constantly changing environmental conditions. C2H2 zinc finger proteins form a relatively large family of transcriptional regulators in plants. Recent studies have revealed that C2H2 zinc finger proteins function as key transcriptional regulators in plant responses to a wide spectrum of stress conditions, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
91
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(94 citation statements)
references
References 67 publications
(118 reference statements)
2
91
0
1
Order By: Relevance
“…During the course of evolution, stress-resistant plants have evolved various physiological and molecular mechanisms to adapt to stress (Sui et al, 2010;Sun et al, 2010;Feng et al, 2014). Halophytes can grow and finish their life cycles in saline soils with a salt concentration equivalent to ≥200mM NaCl (Santos et al, FIGURE 2 | Signaling pathways of C2H2-type zinc finger protein genes involved in abiotic stress responses (Xiong et al, 2002;Wang et al, 2019). 2015; Yuan et al, 2015a;Zhou et al, 2016), and euhalophytes grow vigorously in sea water.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the course of evolution, stress-resistant plants have evolved various physiological and molecular mechanisms to adapt to stress (Sui et al, 2010;Sun et al, 2010;Feng et al, 2014). Halophytes can grow and finish their life cycles in saline soils with a salt concentration equivalent to ≥200mM NaCl (Santos et al, FIGURE 2 | Signaling pathways of C2H2-type zinc finger protein genes involved in abiotic stress responses (Xiong et al, 2002;Wang et al, 2019). 2015; Yuan et al, 2015a;Zhou et al, 2016), and euhalophytes grow vigorously in sea water.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, ABA is responsible for plant defense against abiotic stresses such as salinity, cold, osmotic, drought, active oxygen, and heat (Lata and Prasad, 2011;Ryu and Cho, 2015;Wang et al, 2019). Many studies found that the application of exogenous ABA can induce the expression of many stress related marker genes (Zhu, 2002;Fujita et al, 2013;Nakashima and Yamaguchi-Shinozaki, 2013;Tang et al, 2013).…”
Section: Relationship Of C2h2 Zinc Finger Protein With Hormone Responsementioning
confidence: 99%
“…Notably, nearly 70% of ERF family members were upregulated in the leaves, suggesting that these ERF genes may be more sensitive to drought in common vetch leaves. Moreover, the zinc-finger transcription factor family is another important TF that plays important functions in the response of plants to drought stress [83][84][85]. The overexpression of OsC3H47 promotes drought tolerance and decreases ABA sensitivity in rice [85].…”
Section: The Role Of Tfs In Response To Drought Stressmentioning
confidence: 99%
“…Examples of several TF families found in plants which are important in both biotic and abiotic stress responses are AP2/ERF (APETALA2/ethylene-responsive element binding factor) [7,8], NAC (NAM, ATAF1/2, CUC2) [9,10], bZIP (basic leucine zipper) [11,12], MYB (myeloblastosis) [13,14], WRKY (tryptophan-arginine-lysine-tyrosine) [15,16] and zinc-finger proteins [17][18][19].…”
Section: Introductionmentioning
confidence: 99%